A randomized controlled trial comparing methohexital and propofol for induction in patients receiving angiotensin axis blockade. Issue 5 (February 2019) - Bonavia, Anthony; Verbeek, Thomas; Adhikary, Sanjib; Kunselman, Allen; Budde, Arne; Lyn-Sue, Jerome; Mets, Berend
Abstract: Background: Pharmacologic angiotensin axis blockade (AAB) has been associated with profound hypotension following anesthetic induction with propofol. To combat this problem, investigators have attempted to withhold angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB) preoperatively, or evaluated the effects of different induction agents in conferring greater hemodynamic stability. To date, methohexital has not been compared with the most commonly used induction agent, propofol. Hence, the primary objective was to study the hypothesis that methohexital confers a better hemodynamic profile than propofol for anesthetic induction, in patients receiving AAB. The secondary objective was to investigate the postinduction levels of serum neurohormones in an attempt to explain the mechanisms involved. Methods: Forty-five adult, hypertensive patients taking ACEi or ARB and scheduled for elective, noncardiac surgery completed the study. Patients were randomized to receive equi-anesthetic doses of either propofol or methohexital for anesthetic induction. Hemodynamic variables were measured and blood samples were drawn before induction and for 15 minutes afterwards. Results: Methohexital resulted in less hypotension compared with propofol ( P  = .01), although the degree of refractory hypotension was similar ( P  = .37). The postinduction systolic blood pressure ( P  = .03), diastolic blood pressure ( P  < .001) and heart rate ( P  = .03) were significantly higher in the methohexital group. A nonsignificant elevation of serum norepinephrine and epinephrine levels was observed in the methohexital group, while serum arginine vasopressin and angiotensin II levels did not differ between groups. Conclusion: While methohexital was shown to confer greater hemodynamic stability in patients taking ACEi/ARB, the measured hormone levels could not explain the mechanism for this effect. Abstract : Supplemental Digital Content is available in the text